ANALISIS TINDAK TUTUR DALAM NOVEL AYAT-AYAT CINTA KARYA HABIBURRAHMAN EL SHIRAZY - Gamgulu, Nurmalasari (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2015)
ABSTRACT Speech act is an pragmatics element which involve the speaker, hearer, writer, reader, and the topic. Speech act is a psychology speech from the action and the meaning point of view. It is an identity which play a central role in pragmatics. It is also can be seen the daily activities which has a close relation to a speech act communication in society, public and social. Novel is a prose fiction work that composed in the form of a story. It is a form and result of a creative work and it also uses language in revealing the human life.Pragmatics is a study of meaning in the relation with the speech situations. The aim of this research are to identify the values and to describe the form of speech act which can be found in the novel ‘Ayat-Ayat Cinta’. This research hopefully can enrich the knowledge of the readers in pragmatics aspects of novel and can be the reference for other writers who are eager to write other aspect of pragmatics speech acts. Keywords: Speech acts, Novel, Pragmatics.